LOM for Higher Education OER Repositories: Ein Metadatenprofil für Open Educational Resources im Hochschulbereich zur Förderung der Interoperabilität von OER-Länderrepositorien - Menzel, Michael (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2020)
Initiatives from several federal states in Germany aspire to offer their open licensed and freely available learning materials for higher education in a networked and easily accessable manner.A new metadata profile based on the Learning Object Metadata Standard (LOM) was developed and will serve as a basis for the exchange of metadata. One goal for the profile is to allow a detailed description of the Open Educational Resources (OER) for good search results. On the other hand, only the absolutely necessary information is obligatory in order to keep the obstacles for authors as low as possible.The proposed metadata profile will facilitate a federated search in order to find and use learning materials from connected repositories.
Keywords: Open Educational Resources; Metadata; LOM; Profile; Higher Education; Exchange; Repository